The DEVELOPMENT OF ‘SOFT SKILLS’ THROUGH THE ACTUALIZATION OF THE VOLUNTEER PROJECT ACCORDING TO THE RULES OF CONTEMPLATIVE EDUCATION - Uamsathit, Thapakorn (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2021)
Human beings today are affected by complex societies where there are various stories occur. Fast change may cause problems or lack of efficiency in intellect, spirit, and behavior coexistence with others, which is necessary to develop social skills, known as Soft Skill. The author therefore presents the development of Soft Skills by implementing a volunteer project based on the Rules of Comtemplative Education, which is a wheel-like process with 3 tiers. 1st tier, the core or the core activity, the main drive towards development; 2nd tier, the inner wheel, the self-awareness to transform the inner and 3rd tier, the outer wheel, the external transformation for working with others, which is learning from real experiences that is value to society through self-understanding that causes internal changes and leads to understanding of others, developing external behavior changes and being able to work together with others effectively and happily.